Between Two Rivers - Cartwright, Jacob; Jordan, Nick (United Kingdom, 2012)
Between Two Rivers is a documentary about Cairo, Illinois, a historic river-town with a dark and turbulent past; isolated at the confluence of the Ohio & Mississippi rivers, where North meets South in the heartland of America. Cairo is a town scarred by historic conflicts and bitter divisions. Today, it struggles to survive in the face of economic hardship, depopulation, environmental disasters and a racially segregated past. The film sets Cairo's tumultuous past against the backdrop of the latest crisis to afflict the community: the record-breaking floods of spring 2011, when the rising Ohio & Mississippi rivers threatened to engulf the town.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films